TEACHING SPEAKING SKILL BY USING VIDEO â€œCHECKING-IN HOTELâ€. - Sari, Yunita; ., Sudarsono; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract:The purpose of this research is to describe the effectiveness of the teaching the video â€œchecking in hotelâ€ to improve the studentsâ€™ speaking ability. The subjects of this research are hotel students of SMA Cinta Bumi Khatulistiwa Pontianak in the academic year of 2012/2013. The method of this research is pre-experimental. The data analysis indicated that studentsâ€™ speaking skill improved. The interval mean score of posttest and pretest is 4.68. It means that students gained better speaking skill using video â€œchecking in hotelâ€ score in posttest than that in pretest significantly. The teaching is statistically found effective to improve studentsâ€™ speaking skill, which is not only can relax studentsâ€™ mind, but also keep them active during classroom activity. Keywords: teaching, speaking skill. Â Abstrak: Penelitian ini bertujuan untuk mengetahui efektifitas penggunaan video â€œchecking in hotelâ€ untuk meningkatkan kemampuan berbicara siswa. Subjek Penelitian ini adalah siswa jurusan perhotelan dari SMA Cinta BUmi Khatulistiwa Pontianak tahun akademik 2012/2013. Dalam studi ini, pra-eksperimental adalah metode yang diaplikasikan. Hasil Penelitian menunjukkan bahwa kemampuan berbicara siswa meningkat. Hal ini ditunjukkan oleh interval rerata nilai siswa sebesar 4.68 yang berarti siswa mendapatkan nilai yang cukup signifikan di posttest. Pelmbelajaranmenggunakanmetode inisecarastatistikefektifuntukmeningkatkankemampuanberbicaraparasiswa yang tidak hanya membuat siswa relaks, namun juga tetap aktif selama proses pembelajaran. Â Kata kunci: mengajar, keterampilan berbicara.